Perencanaan Sistem Pemanenan Air Hujan Skala Rumah Tangga Di Korea Selatan - Ha, Park Eun; Susilo, Gatot Eko; Wahono, Endro Prasetyo (Jurnal Rekayasa Sipil dan Desain (JRSDD), 2018)
South Korea is classified as a water shortage country. The government has been promoting a "comprehensive water conservation step" since 2000, and one of the government's programs is to expand the areas that implement the installation of Rainwater Harvesting. This study intend to analyze rainwater harvesting planning system and calculate the cost that must be invested in making rainwater harvesting system according to South Korean standard. Where the water needs to be fulfilled from this research is for flushing water and washing. In this research, hydrological analysis with rainfall data is located in Jeju city from 2007 until 2016, population water requirement and budget cost plan analysis for rainwater harvesting system. From the analysis, the value of water flushing water and laundry for one family can be fulfilled with optimization ratio of 67.75%. The simulation of this research using two cubic meters water tank. The budget plan for construct a rainwater harvesting system for single house is 862,316 won. Base on the simulation this study also could estimate the cost of electric power for the pump of 1130 won per month, therefor for the payment of water which is 30,378 won - 31,613 won can be saved about 30,000 won with the value of NPV of 17,190 won on month 35. Keywords : Jeju City, Rainfall, Water Requirement, Cost, NPV